Ion release from three different dental alloys - effect of dynamic loading and toxicity of released elements - Ketil Hegerstrøm Haugli; Morten Syverud; Jan Tore Samuelsen (Medical Journals Sweden, 2020)
Objective The aims of this in vitro study were to assess if dynamic loading increases the metal ion release of selected dental alloys and to evaluate the cytotoxicity of the released metal ions. Materials and methods One Pd-Ag alloy (Aurolite 2B) and two Co-Cr alloys (Wirobond 280 and d.Sign 30) were investigated. Two different corrosion immersion tests were used: a standardized static test (ISO 22674: 2016) and an experimental dynamic test. Both tests involved immersion of the specimens in a lactic acidic solution (pH = 2.3). Inductively coupled plasma mass spectrometry was used to identify and quantify released elements. A human monocyte cell-line (THP-1) was exposed to serially diluted solutions containing the selected metal ions. Cell viability was measured using the methyl-thiazolyl-tetrazolium assay. Results According to the threshold defined in ISO 22674, only low concentrations of released elements were observed for both corrosion tests. No increase in metal ion release from the dynamic test compared with the static test was observed. Of the released elements, only Zn(II) and Co(II) showed a cytotoxic effect on THP-1 cells at 250 µM and higher concentrations. No increased viability loss was observed when adding other released elements to the exposure mixture. Conclusions The tested alloys showed low levels of metal ion release from both static and dynamic corrosion testing. Dynamic loading did not increase the metal ion release compared to the static corrosion test. Concentrations of 250 µM and above of Zn(II) and Co(II) showed a cytotoxic effect on THP-1 cells.